Replacement of dietary carbohydrate with protein increases fat mass and reduces hepatic triglyceride synthesis and content in female obese Zucker rats - M. Alan Dawson; Stephen R. Hennigar; Mahalakshmi Shankaran; Alyssa M. Kelley; Bradley J. Anderson; Edna Nyangau; Tyler J. Field; William J. Evans; Marc K. Hellerstein; James P. McClung; Stefan M. Pasiakos; Claire E. Berryman (Physiological Reports, 2023)
Abstract Previous studies have demonstrated both energy restriction (ER) and higher protein (HP), lower carbohydrate (LC) diets downregulate hepatic de novo lipogenesis. Little is known about the independent and combined impact of ER and HP/LC diets on tissue‐specific lipid kinetics in leptin receptor‐deficient, obese rodents. This study investigated the effects of ER and dietary macronutrient content on body composition; hepatic, subcutaneous adipose tissue (SAT), and visceral AT (VAT) lipid metabolic flux (2H2O‐labeling); and blood and liver measures of cardiometabolic health in six‐week‐old female obese Zucker rats (Leprfa+/fa+). Animals were randomized to a 10‐week feeding intervention: ad libitum (AL)‐HC/LP (76% carbohydrate/15% protein), AL‐HP/LC (35% protein/56% carbohydrate), ER‐HC/LP, or ER‐HP/LC. ER groups consumed 60% of the feed consumed by AL. AL gained more fat mass than ER (P‐energy = 0.012) and HP/LC gained more fat mass than HC/LP (P‐diet = 0.025). Hepatic triglyceride (TG) concentrations (P‐interaction = 0.0091) and absolute hepatic TG synthesis (P‐interaction = 0.012) were lower in ER‐HP/LC versus ER‐HC/LP. ER had increased hepatic, SAT, and VAT de novo cholesterol fractional synthesis, absolute hepatic cholesterol synthesis, and serum cholesterol (P‐energy≤0.0035). A HP/LC diet, independent of energy intake, led to greater gains in fat mass. A HP/LC diet, in the context of ER, led to reductions in absolute hepatic TG synthesis and TG content. However, ER worsened cholesterol metabolism. Increased adipose tissue TG retention with the HP/LC diet may reflect improved lipid storage capacity and be beneficial in this genetic model of obesity.